COVID-19 emergency: from a general hospital to a covid hospital in one week, an Italian experience - Azzolini, E.; Furia, G.; Cerquetani, F.; Speranza, F.; Chiaradia, S.; Marchianò, V.; Mainelli, M. T.; Vescia, M.; Zoppegno, A.; Quintili, M.; Chierchini, P. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Aim of this letter is to describe the reconversion process of our general hospital, in just one week, into a COVID-19 Hospital. The working strategy allowed to quickly find the spaces, identify the working group, reshape the hospital organizational structure, redesign the flows and patient/health workers pathways. The hospital provided for a progressive activation of COVID-19 beds following the philosophy of the intensity of care. The main results were on management, flows, PPE and hygiene areas. Although some problems came out in the beginning, this fast hospital reconversion model may be replicated in the future to face similar epidemic or pandemic outbreaks.